Past, Present, and Memory: The Ambivalence of Tradition in the Short Stories of Alistair MacLeod - Byrne, Pat (Ethnologies)

(untitled) (Association Canadienne d'Ethnologie et de Folklore, 2008)
The short stories of Alistair MacLeod are strongly influenced by the traditional folk culture of the descendants of the Scots originally displaced by the highland clearances, especially those who settled in Cape Breton. In his treatment of that culture, however, MacLeod develops an ambivalent tension between past and present that results in his characters being caught between the two, tied to the former by memory while struggling to adjust to the demands and harsh realities of the latter.